The Role of Customer Satisfaction in Mediating the Influence of Service Quality on Re-Visit Intention : Study at Natya Hotel Kuta - Made Yoga Saputra; Gede Bayu Rahanatha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Bali is one of the tourist destinations in Indonesia that is most popular with both local and foreign tourists. The high interest of tourists in Bali provides opportunities for hotel industry entrepreneurs in Bali whose growth is increasingly rapid. This research was conducted at Natya Hotel Kuta, Badung. The aim of this research is to explain the role of customer satisfaction in mediating the influence of service quality on re-visit intention. This research uses consumer behavior as a theoretical basis with a sample size of 100 people based on adjusted criteria, using purposive sampling techniques. Data collection in this research was carried out using survey, observation and questionnaire methods via the Google Form platform. This research uses path analysis techniques, Sobel test, and VAF test. The results of this research show that all hypotheses are accepted. Service quality has a positive and significant effect on re-visit intention, service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on re-visit intention and customer satisfaction plays a significant role in mediating the effect of service quality on re-visit intention. visit Intention. The implications of this research can be used by Natya Hotel Kuta to increase customer re-visit intention through the variables of customer satisfaction and service quality.